2019
DOI: 10.1088/1361-6528/ab0d5d
|View full text |Cite
|
Sign up to set email alerts
|

Strain engineering of core–shell silicon carbide nanowires for mechanical and piezoresistive characterizations

Abstract: This study evaluated the mechanical properties and piezoresistivity of core–shell silicon carbide nanowires (C/S-SiCNWs) synthesized by a vapor–liquid–solid technique, which are a promising material for harsh environmental micro electromechanical systems (MEMS) applications. The C/S-SiCNWs were composed of a crystalline cubic (3C) SiC core wrapped by an amorphous silicon dioxide (SiOx) shell; however, TEM observations of the NWs showed that hexagonal polytypes (2H, 4H , and 6H) were partially induced in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…It has been recently observed that similar membrane formation allows heterocellular coupling of cardiac and noncardiac cells in the scar tissue and acts as a possible substrate of heterocellular coupling 38 , and the transfer of mitochondria between stem cells and cardiomyocytes 39 . In our experiments, we compared the MNB formation as triggered by SiO 2 - and SiC-NWs; only semiconducting SiC-NWs supported coupling, because of their conductivity (i.e., ∼11.4 μS cm −1 ) 19 , and therefore impulse propagation over distances. However, SiC-NWs coupled cells had reduced junctional currents compared to physically coupled HL1 cardiomyocytes 40 , but this reduction does not impede the correct AP transfer via MNB formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently observed that similar membrane formation allows heterocellular coupling of cardiac and noncardiac cells in the scar tissue and acts as a possible substrate of heterocellular coupling 38 , and the transfer of mitochondria between stem cells and cardiomyocytes 39 . In our experiments, we compared the MNB formation as triggered by SiO 2 - and SiC-NWs; only semiconducting SiC-NWs supported coupling, because of their conductivity (i.e., ∼11.4 μS cm −1 ) 19 , and therefore impulse propagation over distances. However, SiC-NWs coupled cells had reduced junctional currents compared to physically coupled HL1 cardiomyocytes 40 , but this reduction does not impede the correct AP transfer via MNB formation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, nanomaterials capable of rapidly restoring impulse propagation, with the reinstatement of “physiological cardiac conductivity” are highly desirable. Silicon carbide nanowires (SiC-NWs) have been recognized as a possible candidate for the development of a new generation of implantable nano-devices since they are chemically inert, semiconducting 19 and compatible with the biological environment 20 . In this work, we demonstrate that injectable and biophysically inspired SiC-NWs are capable of electrotonically synchronizing isolated cardiomyocytes via the formation of membrane nanobridges (MNBs) 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several methods based on both top-down and bottomup approaches have been employed to enhance the sensitivity of piezoresistive strain sensors for wider applications. [251][252][253][254] In Figure 10. a) Schematic diagram of "titration-coating" method: (i) original pad; (ii) pad with parafilm; (iii) covered with nanowires; (iv) removed parafilm.…”
Section: Strain Sensorsmentioning
confidence: 99%
“…Very recently, Nakata et al reported another interesting method for improving the sensitivity of sensing devices operating in harsh environments. [254] This method is based on the bottom-up approach in which the core-shell SiC nanowires were synthesized by a VLS technique. Figure 11j,k shows the variations of the resistance change ratio depending on an increase of the tensile strain for the core-shell SiC nanowires and SiC core, respectively.…”
Section: Strain Sensorsmentioning
confidence: 99%
See 1 more Smart Citation